Preparation method of sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure
By preparing hard carbon negative electrode materials rich in graphite-like microcrystalline structures, using hydrogen bonding treatment and multi-step carbonization process, the problem of insufficient sodium storage capacity and electrochemical performance of hard carbon negative electrode materials in sodium ion battery is solved, and high sodium storage is achieved Improved capacity and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411685684.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-01-07
AI Technical Summary
The sodium storage capacity and electrochemical performance of existing sodium ion battery hard carbon anode materials are insufficient, especially due to the tortuous diffusion path of sodium ions, resulting in poor rate performance.
By preparing hard carbon negative electrode materials rich in graphite-like microcrystalline structures, biomass raw materials are crushed, hydrogen bonding, low-temperature carbonization and high-temperature graphitization, hydrogen bonding treatment solvents are used to swell biomass raw materials, and polymers are promoted in the carbonization process The fluidity and rearrangement in the process can form a regular graphite-like layer structure.
It significantly improves the sodium storage capacity and electrochemical performance, shortens the diffusion path of sodium ions, improves the magnification and cycling performance, and simplifies the process flow and enhances the process realization.
Smart Images

Figure CN119263269A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure. Background Art
[0002] Compared with lithium-ion batteries, sodium-ion batteries have the advantages of low manufacturing costs and a wide range of raw material sources, and show great development potential in the fields of large-scale energy storage and low-speed electric vehicles.
[0003] At present, the mainstream technology route for negative electrodes in the commercial development of sodium-ion batteries is hard carbon materials. Hard carbon is amorphous carbon without a fixed crystal structure, and can be considered as a mixed structure consisting of short-range ordered graphite-like microcrystalline regions, amorphous regions, and micropores.
[0004] At present, the research on hard carbon negative electrode materials is mainly focused on improving their sodium storage capacity. The sodium storage capacity of hard carbon materials can be improved by strategies such as graphite-like microcrystal structure regulation or micropore structure regulation. Research has more often used pore-forming agents to enrich the micropore structure of hard carbon materials, thereby improving their sodium storage capacity. However, compared with sodium ions in graphite-like microcrystals, the diffusion path of sodium ions in micropores is more tortuous and the kinetics are slow, resulting in poor rate performance. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a hard carbon negative electrode material for a sodium ion battery rich in a graphite-like microcrystalline structure, which has the characteristics of high sodium storage capacity, excellent electrochemical performance and strong process feasibility.
[0006] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a hard carbon negative electrode material for a sodium ion battery rich in a graphite-like microcrystalline structure, comprising the following steps: S1. Crushing: crushing and sieving the biomass raw materials to obtain refined biomass raw materials; S2, pretreatment: placing the refined biomass raw material obtained in step S1 and the hydrogen bonding treatment solvent in a reaction kettle, controlling the temperature to react fully, filtering and centrifuging to obtain a solvent-swollen biomass raw material; S3, low-temperature carbonization: low-temperature carbonizing the swollen biomass raw material obtained in step S2 under a protective atmosphere to obtain a low-temperature carbonized material; S4, crushing and refining: crushing and refining the low carbonized material obtained in step S3 to obtain a refined low-temperature carbonized material; S5, high temperature graphitization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature graphitization under a protective atmosphere to obtain a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystals.
[0007] Further, in step S2, the hydrogen bond treatment solvent is one or more of ethanol, methanol, ammonia water, ether, formic acid aqueous solution, acetic acid aqueous solution, citric acid aqueous solution, p-hydroxybenzaldehyde aqueous solution, phenol aqueous solution, boric acid aqueous solution, and tetrahydrofuran; this type of hydrogen bond treatment solvent is a solvent that can form hydrogen bonds, and the hydroxyl groups in biomass raw materials such as cellulose, hemicellulose and lignin have a strong attraction to the hydrogen bond treatment solvent molecules. The solvent molecules enter the interior of the biomass molecules under the action of high temperature, causing the biomass to be swollen by the solvent, and the original hydrogen bonds between cellulose, hemicellulose and lignin in the biomass molecules are interrupted, and the solvent molecules form hydrogen bonds with the hydroxyl groups in the biomass molecules to form a bond.
[0008] Furthermore, in step S2, the temperature control reaction conditions are: insulation temperature 40-90°C, insulation time 0.5-5h; higher temperature and longer time can promote the swelling effect of solvent molecules on biomass, but excessively strong swelling effect will cause partial dissolution of biomass molecules and reduce the yield.
[0009] Furthermore, in step S2, the centrifugal frequency is 20-35 Hz, the centrifugal time is 10-30 min, and the amount of solvent retained inside the biomass material is 5-20 wt.% of its own weight; if the centrifugal frequency is too high or the centrifugal time is too long, the amount of solvent retained inside the biomass material is too low, which is not conducive to the subsequent growth and rearrangement of the carbon layer; conversely, if the amount of solvent retained inside the biomass is too high, the degree of graphitization of the formed carbon layer is too high, which is also not conducive to the performance of the hard carbon performance.
[0010] Further, in step S3, the protective atmosphere is nitrogen and / or argon, the heating rate during the carbonization process is 5-20°C / min, the carbonization temperature is 300-900°C, and the carbonization time is 2-5 h. Specifically, the hydrogen bonds between the cellulose, hemicellulose and lignin molecules inside the biomass particles are destroyed, and the hydroxyl groups inside the biomass molecules are combined with the solvent molecules with good fluidity to form hydrogen bonds, so that the polymers inside the biomass have good fluidity, and are easy to migrate and rearrange under the action of thermodynamics to form a better graphite-like layer structure during the carbonization process. At the same time, the heating rate and carbonization temperature will affect the effect of the present invention: if the heating rate is slow or the carbonization temperature is too high, the organic solvent is easy to gasify and volatilize out of the molecule, and the purpose of the present invention cannot be achieved; if the carbonization temperature is too low, the kinetics of the carbon molecules are slow and are not conducive to their graphitization rearrangement.
[0011] Further, in step S5, the protective atmosphere is nitrogen and / or argon, the heating rate during graphitization is 1-15°C / min, the graphitization temperature is 1100-1500°C, and the graphitization time is 2-5 h.
[0012] Further, in step S1, the biomass raw material is one or more of walnut shells, nut shells, apricot shells, straw, reed, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, and oak. Specifically, the main components of biomass are three types of high molecular polymers, namely cellulose, hemicellulose, and lignin. Cellulose molecules are arranged regularly to form the framework of the cell wall, and hemicellulose and lignin are filled between the frameworks. The combination between cellulose, hemicellulose, and lignin molecules mainly depends on intermolecular hydrogen bonds. The intermolecular hydrogen bond force is strong, resulting in tight cross-linking between molecules, so the migration ability of molecules during pyrolysis is poor, and it is difficult to rearrange to form a more regular graphite-like microcrystalline structure.
[0013] Furthermore, in step S1, the mesh number of the sieve is ≥ 10. If the mesh number of the sieve is too small, the biomass particles are relatively large, and the solvent is not easy to penetrate into the interior of the biomass, and the purpose of moistening and expanding the macromolecules in the biomass cannot be achieved.
[0014] Furthermore, in step S4, the pulverizing method is one or more of jaw crusher, roller mill, mechanical mill, Raymond mill, air flow mill, ball mill, stirred mill and sand mill, and the particle size of the low temperature carbonized material is controlled to be 4-10 μm.
[0015] Another aspect of the present invention is to protect a hard carbon negative electrode material for a sodium ion battery, wherein the negative electrode material is prepared by the above-mentioned preparation method.
[0016] The present invention provides a method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure, which has the following beneficial effects: First, the sodium storage capacity is high. The hydrogen bonding between cellulose, hemicellulose and lignin in the biomass raw materials is destroyed by the swelling of the solvent molecules through hydrogen bonding treatment, so that the polymer inside the biomass has better fluidity during the carbonization process, and is more likely to migrate and rearrange under the action of thermodynamics to form a rich graphite-like layer structure, thereby improving the sodium storage capacity of the hard carbon material; Second, the electrochemical performance is excellent, and the graphite-like microstructure is relatively regular, so the diffusion path of sodium ions in it is short, the kinetics are more stable, and it shows better rate and cycle performance, thus effectively improving the electrochemical performance of hard carbon negative electrode materials for sodium ion batteries; Third, the process is highly feasible. Compared with the conventional biomass hard carbon negative electrode material preparation method, the preparation method of the present invention introduces hydrogen bond treatment solvents for expansion treatment in terms of supply and demand to improve the degree of graphitization. No tedious treatment is required, which effectively ensures the feasibility of the process. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Attached Figure 1 This is a TEM image of Application Example 1 of a method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure according to the present invention; Attached Figure 2 This is a TEM image of comparative example 1 of a method for preparing a sodium ion battery hard carbon negative electrode material rich in a graphite-like microcrystalline structure according to the present invention. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0019] The present invention discloses a method for preparing a hard carbon negative electrode material for a sodium ion battery rich in a graphite-like microcrystalline structure, comprising the following steps: S1. Crushing: crushing and sieving the biomass raw materials to obtain refined biomass raw materials; S2, pretreatment: placing the refined biomass raw material obtained in step S1 and the hydrogen bonding treatment solvent in a reaction kettle, controlling the temperature to react fully, filtering and centrifuging to obtain a solvent-swollen biomass raw material; S3, low-temperature carbonization: low-temperature carbonizing the swollen biomass raw material obtained in step S2 under a protective atmosphere to obtain a low-temperature carbonized material; S4, crushing and refining: crushing and refining the low carbonized material obtained in step S3 to obtain a refined low-temperature carbonized material; S5, high temperature graphitization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature graphitization under a protective atmosphere to obtain a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystals.
[0020] Further, in step S2, the hydrogen bond treatment solvent is one or more of ethanol, methanol, ammonia water, ether, formic acid aqueous solution, acetic acid aqueous solution, citric acid aqueous solution, p-hydroxybenzaldehyde aqueous solution, phenol aqueous solution, boric acid aqueous solution, and tetrahydrofuran.
[0021] Furthermore, in step S2, the temperature control reaction conditions are: insulation temperature 40-90°C, insulation time 0.5-5h.
[0022] Furthermore, in step S2, the centrifugal frequency is 20-35 Hz, the centrifugal time is 10-30 min, and the amount of solvent retained inside the biomass material is 5-20 wt.% of its own weight.
[0023] Further, in step S3, the protective atmosphere is nitrogen and / or argon, the heating rate during the carbonization process is 5-20°C / min, the carbonization temperature is 300-900°C, and the carbonization time is 2-5 h.
[0024] Further, in step S5, the protective atmosphere is nitrogen and / or argon, the heating rate during graphitization is 1-15°C / min, the graphitization temperature is 1100-1500°C, and the graphitization time is 2-5 h.
[0025] Furthermore, in step S1, the biomass raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, and oak.
[0026] Further, in step S1, the mesh number of the sieve is ≥10 meshes.
[0027] Furthermore, in step S4, the pulverizing method is one or more of jaw crusher, roller mill, mechanical mill, Raymond mill, air flow mill, ball mill, stirred mill and sand mill, and the particle size of the low temperature carbonized material is controlled to be 4-10 μm.
[0028] Another aspect of the present invention is to protect a hard carbon negative electrode material for a sodium ion battery, wherein the negative electrode material is prepared by the above-mentioned preparation method.
[0029] Example 1 This embodiment relates to a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure, and its preparation method comprises the following steps: S1. Crushing: crushing and sieving the biomass raw materials to obtain refined biomass raw materials. The biomass raw materials are walnut shells, nut shells, and apricot shells; the mesh number of the sieve is ≥10 meshes.
[0030] S2. Pretreatment: The refined biomass raw material obtained in step S1 and the hydrogen bonding treatment solvent are placed in a reactor, and after the temperature is controlled to react fully, the biomass raw material is filtered and centrifuged to obtain a solvent-swollen biomass raw material. Specifically, the hydrogen bonding treatment solvent is ethanol, methanol, and ammonia water; the temperature control reaction conditions are: the insulation temperature is 90°C, the insulation time is 3h; the centrifugal frequency is 20Hz, the centrifugal time is 30min, and the amount of solvent retained inside the biomass material is 12wt.% of its own weight.
[0031] S3, low temperature carbonization: the swollen biomass raw material obtained in step S2 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material. Specifically, the protective atmosphere is nitrogen, the heating rate during the carbonization process is 5°C / min, the carbonization temperature is 900°C, and the carbonization time is 3 hours.
[0032] S4, crushing and refining: crushing and refining the low carbonized material obtained in step S3 to obtain refined low temperature carbonized material. Specifically, the crushing method is jaw crusher and roller crusher, and the particle size of the low temperature carbonized material is controlled to be 4-10 μm.
[0033] S5, high temperature graphitization: The refined low temperature carbonized material obtained in step S4 is subjected to high temperature graphitization under a protective atmosphere to obtain a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystals. Specifically, the protective atmosphere is argon, the heating rate during the graphitization process is 1 ° C / min, the graphitization temperature is 1500 ° C, and the graphitization time is 3 h.
[0034] Example 2 This embodiment relates to a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure, and its preparation method comprises the following steps: S1. Crushing: crush and sieve the biomass raw materials to obtain refined biomass raw materials. The biomass raw materials are miscellaneous wood, fir, and oak; the mesh number of the sieve is ≥10 mesh.
[0035] S2. Pretreatment: The refined biomass raw material obtained in step S1 and the hydrogen bonding treatment solvent are placed in a reactor, and after the temperature-controlled reaction is sufficient, the biomass raw material is filtered and centrifuged to obtain a solvent-swollen biomass raw material. Specifically, the hydrogen bonding treatment solvent is a phenol aqueous solution, a boric acid aqueous solution, and tetrahydrofuran; the temperature-controlled reaction conditions are: a heat preservation temperature of 70°C and a heat preservation time of 0.5h; a centrifugal frequency of 35Hz and a centrifugal time of 20min, and the amount of solvent retained inside the biomass material is 5wt.% of its own weight.
[0036] S3, low temperature carbonization: the swollen biomass raw material obtained in step S2 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material. Specifically, the protective atmosphere is argon, the heating rate during the carbonization process is 20°C / min, the carbonization temperature is 600°C, and the carbonization time is 2 hours.
[0037] S4, crushing and refining: crushing and refining the low carbonized material obtained in step S3 to obtain refined low temperature carbonized material. Specifically, the crushing method is air flow powder and sand milling, and the particle size of the low temperature carbonized material is controlled to be 4-10 μm.
[0038] S5, high temperature graphitization: The refined low temperature carbonized material obtained in step S4 is subjected to high temperature graphitization under a protective atmosphere to obtain a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystals. Specifically, the protective atmosphere is nitrogen and argon, the heating rate during the graphitization process is 15 ° C / min, the graphitization temperature is 1300 ° C, and the graphitization time is 2 h.
[0039] Example 3 This embodiment relates to a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure, and its preparation method comprises the following steps: S1. Crushing: crushing and sieving the biomass raw materials to obtain refined biomass raw materials. The biomass raw materials are apricot shells, straw, reeds, and coffee shells; the mesh number of the sieve is ≥10 meshes.
[0040] S2. Pretreatment: placing the refined biomass raw material obtained in step S1 and the hydrogen bonding treatment solvent in a reactor, controlling the temperature to react fully, filtering and centrifuging to obtain the solvent-swollen biomass raw material. Specifically, the hydrogen bonding treatment solvent is a citric acid aqueous solution and a p-hydroxybenzaldehyde aqueous solution; the temperature control reaction conditions are: the insulation temperature is 40°C and the insulation time is 5h; the centrifugal frequency is 30Hz and the centrifugal time is 10min, and the amount of solvent retained in the biomass material is 20wt.% of its own weight.
[0041] S3, low temperature carbonization: the swollen biomass raw material obtained in step S2 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material. Specifically, the protective atmosphere is nitrogen and argon, the heating rate during the carbonization process is 12 °C / min, the carbonization temperature is 300 °C, and the carbonization time is 5 h.
[0042] S4, crushing and refining: crushing and refining the low carbonized material obtained in step S3 to obtain refined low-temperature carbonized material. Specifically, the crushing method is ball milling, stirring milling, and sand milling, and the particle size of the low-temperature carbonized material is controlled to be 4-10 μm.
[0043] S5, high temperature graphitization: The refined low temperature carbonized material obtained in step S4 is subjected to high temperature graphitization under a protective atmosphere to obtain a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystals. Specifically, the protective atmosphere is nitrogen and / or argon, the heating rate during the graphitization process is 1 ° C / min, the graphitization temperature is 1500 ° C, and the graphitization time is 3 h.
[0044] Example 4 This embodiment relates to a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure, and its preparation method comprises the following steps: S1. Crushing: crush and sieve the biomass raw materials to obtain refined biomass raw materials. The biomass raw materials are walnut shells, nut shells, apricot shells, straw, eucalyptus, pine, fruit wood, and miscellaneous wood; the mesh number of the sieve is ≥10 mesh.
[0045] S2. Pretreatment: The refined biomass raw material obtained in step S1 and the hydrogen bonding treatment solvent are placed in a reactor, and after the temperature is controlled to react fully, the biomass raw material is filtered and centrifuged to obtain a solvent-swollen biomass raw material. Specifically, the hydrogen bonding treatment solvent is ethanol, methanol, phenol aqueous solution, boric acid aqueous solution, tetrahydrofuran; the temperature control reaction conditions are: insulation temperature 80°C, insulation time 1h; centrifugation frequency 35Hz, centrifugation time 25min, and the amount of solvent retained inside the biomass material is 10wt.% of its own weight.
[0046] S3, low temperature carbonization: the swollen biomass raw material obtained in step S2 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material. Specifically, the protective atmosphere is nitrogen and argon, the heating rate during the carbonization process is 10°C / min, the carbonization temperature is 400°C, and the carbonization time is 4 hours.
[0047] S4, crushing and refining: crushing and refining the low carbonized material obtained in step S3 to obtain refined low temperature carbonized material. Specifically, the crushing method is grinding and sand grinding, and the particle size of the low temperature carbonized material is controlled to be 4-10 μm.
[0048] S5, high temperature graphitization: The refined low temperature carbonized material obtained in step S4 is subjected to high temperature graphitization under a protective atmosphere to obtain a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystals. Specifically, the protective atmosphere is nitrogen and argon, the heating rate during the graphitization process is 5 ° C / min, the graphitization temperature is 1200 ° C, and the graphitization time is 4 h.
[0049] Example 5 This embodiment relates to a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure, and its preparation method comprises the following steps: S1. Crushing: crush and sieve the biomass raw materials to obtain refined biomass raw materials. The biomass raw materials are walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, and poplar wood; the mesh number of the sieve is ≥10 meshes.
[0050] S2. Pretreatment: The refined biomass raw material obtained in step S1 and the hydrogen bonding treatment solvent are placed in a reactor, and after the temperature is controlled to react fully, the biomass raw material is filtered and centrifuged to obtain a solvent-swollen biomass raw material. Specifically, the hydrogen bonding treatment solvent is ethanol, methanol, ammonia water, ether, and formic acid aqueous solution; the temperature control reaction conditions are: the insulation temperature is 50°C, the insulation time is 3h; the centrifugal frequency is 25Hz, the centrifugal time is 15min, and the amount of solvent retained in the biomass material is 15wt.% of its own weight.
[0051] S3, low temperature carbonization: the swollen biomass raw material obtained in step S2 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material. Specifically, the protective atmosphere is nitrogen and argon, the heating rate during the carbonization process is 15°C / min, the carbonization temperature is 500°C, and the carbonization time is 3 hours.
[0052] S4, crushing and refining: crushing and refining the low carbonized material obtained in step S3 to obtain refined low temperature carbonized material. Specifically, the crushing method is air flow pulverization, ball milling, stirring milling, sand milling, and the particle size of the low temperature carbonized material is controlled to be 4-10 μm.
[0053] S5, high temperature graphitization: The refined low temperature carbonized material obtained in step S4 is subjected to high temperature graphitization under a protective atmosphere to obtain a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystals. Specifically, the protective atmosphere is nitrogen and argon, the heating rate during the graphitization process is 5 ° C / min, the graphitization temperature is 1400 ° C, and the graphitization time is 3 h.
[0054] Application Example 1 This embodiment relates to a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure, and its preparation method comprises the following steps: S1. Crushing: crush the walnut shell raw material and pass it through a 10-mesh sieve to obtain walnut shell raw material of a certain fineness.
[0055] S2, pretreatment: the walnut shell raw material of a certain fineness obtained in step S1 and ethanol are placed in a reactor, kept warm at 60° C. for 3 hours, then filtered, and centrifuged at 30 Hz for 15 minutes in a centrifuge to obtain an ethanol-swollen walnut shell raw material with an ethanol content of 15 wt.%.
[0056] S3, low-temperature carbonization: the ethanol-swollen walnut shell raw material obtained in step S2 is subjected to low-temperature carbonization under a nitrogen atmosphere, the heating rate during the carbonization process is 10°C / min, the carbonization temperature is 650°C, and the carbonization time is 3 h to obtain a low-temperature carbonized material.
[0057] S4, pulverizing and refining: the low carbonized material obtained in step S3 is pulverized by rollers and air flow powder in turn to obtain a low-temperature carbonized material with a D50 of 7 μm.
[0058] S5. High-temperature graphitization: The low-temperature carbonized material obtained in step S4 is subjected to high-temperature graphitization in a nitrogen atmosphere. The heating rate during the graphitization process is 5°C / min, the temperature is 1300°C, and the time is 3 h, to obtain the hard carbon negative electrode material of Application Example 1.
[0059] Application Example 2 This embodiment relates to a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure, and its preparation method comprises the following steps: S1. Crushing: crush the walnut shell raw material and pass it through a 10-mesh sieve to obtain walnut shell raw material of a certain fineness.
[0060] S2, pretreatment: the walnut shell raw material of a certain fineness obtained in step S1 and ammonia water are placed in a reactor, kept warm at 60° C. for 3 hours, then filtered, and centrifuged at 30 Hz for 15 minutes in a centrifuge to obtain an ammonia water-swollen walnut shell raw material with an ethanol content of 15 wt.%.
[0061] S3, low-temperature carbonization: the walnut shell raw material swollen with ammonia water obtained in step S2 is subjected to low-temperature carbonization under a nitrogen atmosphere, the heating rate during the carbonization process is 10°C / min, the carbonization temperature is 650°C, and the carbonization time is 3 h to obtain a low-temperature carbonized material.
[0062] S4, pulverizing and refining: the low carbonized material obtained in step S3 is pulverized by rollers and air flow powder in turn to obtain a low-temperature carbonized material with a D50 of 7 μm.
[0063] S5. High-temperature graphitization: The low-temperature carbonized material obtained in step S4 is subjected to high-temperature graphitization in a nitrogen atmosphere. The heating rate during the graphitization process is 5°C / min, the temperature is 1300°C, and the time is 3 h, to obtain the hard carbon negative electrode material of Application Example 2.
[0064] Comparative Example 1 This embodiment relates to a hard carbon negative electrode material for a sodium ion battery, and a preparation method thereof comprises the following steps: S1. Crushing: crush the walnut shell raw material and pass it through a 10-mesh sieve to obtain walnut shell raw material of a certain fineness.
[0065] S2, pretreatment: placing the walnut shell raw material of a certain fineness obtained in step S1 in a reaction kettle, and keeping it warm at 60° C. for 3 hours to obtain a pretreated walnut shell raw material.
[0066] S3, low-temperature carbonization: the walnut shell raw material obtained in step S2 is subjected to low-temperature carbonization under a nitrogen atmosphere, the heating rate during the carbonization process is 10°C / min, the carbonization temperature is 650°C, and the carbonization time is 3 h to obtain a low-temperature carbonized material.
[0067] S4, pulverizing and refining: the low carbonized material obtained in step S3 is pulverized by rollers and air flow powder in turn to obtain a low-temperature carbonized material with a D50 of 7 μm.
[0068] S5. High-temperature graphitization: The low-temperature carbonized material obtained in step S4 is subjected to high-temperature graphitization in a nitrogen atmosphere. During the graphitization process, the heating rate is 5°C / min, the temperature is 1300°C, and the time is 3 h to obtain the hard carbon negative electrode material of comparative example 1.
[0069] Raman test was used to characterize the graphitization degree of Example 1, Example 2 and Comparative Example 1. Raman test results showed that the Id / Ig values of Example 1, Example 2 and Comparative Example 1 were 1.68, 1.73 and 1.92, respectively, indicating that the solvent swelling effect of forming hydrogen bonds can effectively promote the graphitization degree of hard carbon materials.
[0070] Figure 1 and Figure 2They are high-resolution TEM images of Application Example 1 and Comparative Example 1. As can be seen from the figure, Application Example 1 has more obvious and clear lattice fringes, which further proves that Application Example 1 has a higher degree of graphitization and rich graphite-like microcrystalline structure.
[0071] The constant current charge and discharge test measured that the first week charging specific capacities of Application Example 1, Application Example 2 and Comparative Example 1 were 351, 342 and 296 mAh / g, respectively, indicating that the rich graphite-like microcrystalline structure inside the hard carbon material can effectively improve its sodium storage capacity.
[0072] In the cycle performance test, the capacity retention rates of Application Example 1, Application Example 2 and Comparative Example 1 after 100 cycles at a current density of 500 mA / g were 94.3%, 93.6% and 89.4%, respectively, indicating that hard carbon rich in graphite-like microcrystals has good cycle performance.
[0073] In the rate performance test, the capacity retention rates of Application Example 1, Application Example 2 and Comparative Example 1 at a rate of 5C were 84.3%, 83.6% and 76.4%, respectively, indicating that hard carbon rich in graphite-like microcrystals has better rate performance.
[0074] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A method for preparing a hard carbon negative electrode material for a sodium ion battery rich in graphite-like microcrystalline structure, characterized in that The following steps are involved: S1. Crushing: crushing and sieving the biomass raw materials to obtain refined biomass raw materials; S2, pretreatment: placing the refined biomass raw material obtained in step S1 and the hydrogen bonding treatment solvent in a reaction kettle, controlling the temperature to react fully, filtering and centrifuging to obtain a solvent-swollen biomass raw material; S3, low-temperature carbonization: low-temperature carbonizing the swollen biomass raw material obtained in step S2 under a protective atmosphere to obtain a low-temperature carbonized material; S4, crushing and refining: crushing and refining the low carbonized material obtained in step S3 to obtain a refined low-temperature carbonized material; S5, high temperature graphitization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature graphitization under a protective atmosphere to obtain a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystals.
2. The method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure according to claim 1, characterized in that: In step S2, the hydrogen bonding treatment solvent is one or more of ethanol, methanol, ammonia water, ether, formic acid aqueous solution, acetic acid aqueous solution, citric acid aqueous solution, p-hydroxybenzaldehyde aqueous solution, phenol aqueous solution, boric acid aqueous solution, and tetrahydrofuran.
3. The method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure according to claim 1, characterized in that: In step S2, the temperature control reaction conditions are: insulation temperature 40-90°C, insulation time 0.5-5h.
4. The method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure according to claim 1, characterized in that: In step S2, the centrifugal frequency is 20-35 Hz, the centrifugal time is 10-30 min, and the amount of solvent retained in the biomass material is 5-20 wt.% of its own weight.
5. The method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure according to claim 1, characterized in that: In step S3, the protective atmosphere is nitrogen and / or argon, the heating rate during the carbonization process is 5-20°C / min, the carbonization temperature is 300-900°C, and the carbonization time is 2-5 h.
6. The method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure according to claim 1, characterized in that: In step S5, the protective atmosphere is nitrogen and / or argon, the heating rate during graphitization is 1-15°C / min, the graphitization temperature is 1100-1500°C, and the graphitization time is 2-5 h.
7. The method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure according to claim 1, characterized in that: In step S1, the biomass raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, and oak.
8. The method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure according to claim 1, characterized in that: In step S1, the mesh number of the sieve is ≥10 meshes.
9. The method for preparing a sodium ion battery hard carbon negative electrode material rich in graphite-like microcrystalline structure according to claim 1, characterized in that: In step S4, the pulverizing method is one or more of jaw crusher, roller mill, mechanical mill, Raymond mill, air flow mill, ball mill, stirred mill and sand mill, and the particle size of the low temperature carbonized material is controlled to be 4-10 μm.
10. A hard carbon negative electrode material for a sodium ion battery, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Waste biomass kernel derived hard carbon material as well as preparation method and application thereof
CN115863634A